PELAKSANAAN PEMERIKSAAN OLAH TEMPAT KEJADIAN PERKARA (TKP) DALAM PROSES PENYIDIKAN KECELAKAAN LALU LINTAS - Harry Kurniawan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The legal regulation governing the implementation of the scene of the incident in the investigation of traffic accidents is Article 35 paragraph 1 concerning Regulation of the Chief of Police of the Republic of Indonesia Number 15 of 2013 junto Law Number 22 of 2009 concerning Road Traffic and Transportation. The implementation of the implementation of traffic accident investigations is to record and prepare to visit the scene of a traffic accident case. Go to the scene, processing the crime scene, traffic accident and termination of handling the traffic accident scene Termination is the final step in handling the traffic accident scene. Factors that become obstacles in the investigation of traffic accidents are the human factor, in this case what causes damage so that obstacles in the investigation process are the community, suspects and people who are not interested, natural factors in the form of rain, wind, dew, delays in reporting received from the parties concerned.